2001
DOI: 10.1073/pnas.161269798
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and DNA damage induced by Cre recombinase in mammalian cells

Abstract: The use of Cre͞loxP recombination in mammalian cells has expanded rapidly. We describe here that Cre expression in cultured mammalian cells may result in a markedly reduced proliferation and that this effect is dependent on the endonuclease activity of Cre. Chromosome analysis after Cre expression revealed numerous chromosomal aberrations and an increased number of sister chromatid exchanges. Titration experiments in mouse embryo fibroblasts with a ligand-regulatable Cre-ER T show that toxicity is dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
473
3
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(517 citation statements)
references
References 40 publications
34
473
3
1
Order By: Relevance
“…In this context, oncogenic lesions that arise from stresses other than DSBs in Tp53 À/À cells before lymphocyte lineage commitment and/or in developing T lineage lymphocytes might drive thymocyte transformation more effectively than translocations that arise in B lineage cells. Although cre expression in cultured mouse embryonic cells causes genomic instability (Loonstra et al, 2001;Silver and Livingston, 2001), constitutive cre expression initiating in thymocytes neither leads to a detectable increase in genomic instability nor accelerates the development of thymic lymphomas in Tp53 À/À mice (Cheung et al, 2002). Still, it is possible that mb1-cre expression causes oncogenic translocations or other lesions that cooperate with RAG/AID-initiated translocations to accelerate the transformation of Tp53-deficient B lineage cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, oncogenic lesions that arise from stresses other than DSBs in Tp53 À/À cells before lymphocyte lineage commitment and/or in developing T lineage lymphocytes might drive thymocyte transformation more effectively than translocations that arise in B lineage cells. Although cre expression in cultured mouse embryonic cells causes genomic instability (Loonstra et al, 2001;Silver and Livingston, 2001), constitutive cre expression initiating in thymocytes neither leads to a detectable increase in genomic instability nor accelerates the development of thymic lymphomas in Tp53 À/À mice (Cheung et al, 2002). Still, it is possible that mb1-cre expression causes oncogenic translocations or other lesions that cooperate with RAG/AID-initiated translocations to accelerate the transformation of Tp53-deficient B lineage cells.…”
Section: Resultsmentioning
confidence: 99%
“…For abbreviations, see Table 1. pathologic condition further, however, it is possible that overexpression of Cre could be deleterious to neurons, as Cre expression has been shown to be toxic to cells in culture and in transgenic mice (Schmidt et al, 2000;Loonstra et al, 2001). Gene ablation by using the Cre-loxP system requires that Cre expression is spatially and temporally restricted to the tissue of interest, especially if one is studying the effects of ablating genes whose expression is widespread.…”
Section: Resultsmentioning
confidence: 99%
“…Similar toxicity issues do exist for the Cre-loxP system also. Loonstra et al 51 have shown that Cre recombinase expression in cultured mammalian cells may result in a markedly reduced proliferation and also numerous chromosomal aberrations and an increased number of sister chromatid exchanges. However, they also demonstrated that the toxicity is dependent on the level of Cre recombinase activity.…”
Section: Discussionmentioning
confidence: 99%